Compliance of the Nurse for Fall Risk Re-Assessment Base on Theory of Planned Behaviour - Putrina, Ade; Harmayetty, Harmayetty; Krisnana, Ilya (Fundamental and Management Nursing Journal, 2019)
Introduction: Increasing the workload of nurses caused the re-assessment of patients fall risk to be rare and can affect the value and quality of the Hospital. This study aims to determine the factors associated with patient compliance with re-assessment of the risk of falls in IRNA Bedah RSUD Dr. Soetomo Surabaya.Method: This study uses a descriptive correlation design with a cross-sectional approach. Samples in this research was nurses obtained with simple random sampling. Independent variables were attitudes, subjective norms, perceived behavior control, and intention. The dependent variable was compliance with re-assessment of the patient's fall risk. Data were obtained by attitude, subjective norms, perceived behavior control, intention, and compliance with re-assessment questionnaires and analyzed with Spearman's Rho with α = 0,05%.Result: Statistical test results showed that there was a significant relationship (p = 0.010) between attitudes and nurses' intentions in re-assessment of risky patients with weak correlation levels (r = -0.292), there was a significant relationship (p = 0.001) between Subjective norms with nurse intentions on re-assessment of falling risk patients with weak correlation levels (r = 0.281), there is a significant relationship (p = 0.007) between perceived behavioral control and nurses' intentions on re-assessment of falling risk patients with weak correlation levels ( r = 0.237), there is a significant relationship (p = 0,000) between intention and nurse adherence in re-assessment of patients' risk of falling with a fairly strong correlation level (r = 0.541).Conclussion: Intention has the strongest relationship in reassessing falling risk patients. Attitudes, subjective norms, and perceived behavioral control also be a factor in increasing nurse participation in reassessing a patient's risk of falling. Supervision and control of nurses' approval is needed in reassessing patients at risk of falling.